The Effect of Health Education Based on Islamic Teachings on Knowledge Level of Toddlers’ Parents Regarding Singapore Flu - Siwi, Ignasia Nila (Journal of Health Sciences, 2024)
HFMD is an infectious disease that occurs in children under five, especially at school or daycare. This research aims to determine the effect of providing health education according to Islamic teachings on the level of parents' knowledge about HFMD in toddlers. The research design used Quasi-Experimental with Group Pretest and Post Test Design. The sample in this research was 22 respondents with a total sampling technique. The analysis used in this research was univariate analysis and paired t-test analysis. The results of the study used the paired t-test and found that there were significant differences in the pretest and posttest values of parents' knowledge about HFMD in children under five with a p-value of 0.000 (<0.05). This research concluded that there was an effect of providing health education according to Islamic teachings on the level of parents' knowledge about HFMD in children under five.